2019
DOI: 10.1293/tox.2019-0004
|View full text |Cite
|
Sign up to set email alerts
|

Brain findings associated with risperidone in rhesus monkeys: magnetic resonance imaging and pathology perspectives

Abstract: Brain changes associated with risperidone, a dopamine-2/serotonin-2 receptor antagonist, have been documented in rats and humans, but not in nonhuman primates. This study characterized brain changes associated with risperidone in nonhuman primates. Rhesus monkeys were orally administered risperidone in a dose-escalation paradigm up to a maximum tolerated dose of 0.5 mg/kg/day for 3 weeks, or 3 months followed by a 3-month recovery period. Transient and fully reversible neurological signs consistent with risper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…monkeys, and humans (Toro et al, 2006;Bernstein et al, 2014;Fernandez et al, 2019). In rhesus monkeys, the effect of risperidone was restricted to the striatum as histological staining showed reversible increase in staining in the cell bodies as well as processes of putamen astrocytes (Fernandez et al, 2019). Another dopamine receptor blocker, haloperidol, was shown to block D2 receptors on astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…monkeys, and humans (Toro et al, 2006;Bernstein et al, 2014;Fernandez et al, 2019). In rhesus monkeys, the effect of risperidone was restricted to the striatum as histological staining showed reversible increase in staining in the cell bodies as well as processes of putamen astrocytes (Fernandez et al, 2019). Another dopamine receptor blocker, haloperidol, was shown to block D2 receptors on astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study reported that rhesus monkeys orally receiving risperidone in a dose-escalation method up to the dose of 0.5 mg/kg/day for 21 days reveal no risperidone-related brain weight changes or gross findings by magnetic resonance imaging (MRI). Although glial fibrillary acidic protein (GFAP) was detected in the brain of these monkeys after 21 days and 12 weeks, no increased GFAP staining was observed after the 12-week recovery period, suggesting this reversible increase of GFAP is likely an adaptive, non-adverse response of astrocytes ( Fernandez et al, 2019 ). In this study, the effective risperidone dose for xenograft tumor experiments is similar to those reported in the study of rhesus monkeys ( Fernandez et al, 2019 ).…”
Section: Discussionmentioning
confidence: 95%
“…Although glial fibrillary acidic protein (GFAP) was detected in the brain of these monkeys after 21 days and 12 weeks, no increased GFAP staining was observed after the 12-week recovery period, suggesting this reversible increase of GFAP is likely an adaptive, non-adverse response of astrocytes ( Fernandez et al, 2019 ). In this study, the effective risperidone dose for xenograft tumor experiments is similar to those reported in the study of rhesus monkeys ( Fernandez et al, 2019 ). Therefore, this finding may suggest a possibility that higher-dose of risperidone can be used in treatments of gastric cancer.…”
Section: Discussionmentioning
confidence: 95%